(untitled) (CAHIERS MAGELLANES-NS, 2024)
Purpose- The objective of this study was to study customer satisfaction with different dairy brands. Theoretical Framework- However studies have been done related to customer satisfaction and this study is framed to explore whether a company has met the needs of its customers and whether those customers are happy with the service they received from dairy brands. Design/Methodology/Approach- In this study, the researcher used non-probability sampling techniques by judgmental sampling for data collection. By using a survey questionnaire, data were collected from 100 customers using any dairy brand in Haryana. The SPSS version 25.0 is castoff as an analytical tool in this research. Findings- It has been concluded that Vita and Modern dairy products are highly satisfying the needs of customers because they are engaged in the services of customers and producing the goods according to the needs of the markets and it is shown that Vita and Modern dairy gives a clear image that customer feel good about product and service. Research, Practical and Social Implications- Future studies can be considered towards impact and some other gauges for dairy industries and the researchers conduct the study with more sample size, varied location. Implications/Originality/value- It is concluded that customer satisfaction is the one dimension that changes due to the changes in marketing trends.